2014
DOI: 10.1097/hjh.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–9) reverses experimental hypertension and cardiovascular damage by inhibition of the angiotensin converting enzyme/Ang II axis

Abstract: Angiotensin-(1-9) reduces hypertension, ameliorates structural alterations (hypertrophy and fibrosis), oxidative stress in the heart and aorta and improves cardiac and endothelial function in hypertensive rats. These effects were mediated by the AT2 receptor but not by the angiotensin-(1-7)/Mas receptor axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 48 publications
6
80
0
9
Order By: Relevance
“…Recientemente, Flores-Muñoz et al, mostró en su modelo experimental de ratas "strole-prone" espontáneamente hipertensas (SPSHR) que Ang-(1-9) administrada en dosis de 100 ng·Kg-1·min-1 no modificó la PAS 22 . Estos resultados difieren del efecto antihipertensivo observado para Ang-(1-9) probablemente, debido a la menor dosis de Ang-(1-9) usada en ratas SPSHR comparada con nuestros estudios de regresión de la HTA 23 . Por otra parte, los resultados del presente estudio muestran que la administración crónica de Ang-(1-9), en un modelo experimental de ratas previamente hipertensas, logró revertir la hipertrofia cardíaca, destacando que este efecto tampoco fue mediado por Ang-(1-7).…”
Section: Discussionunclassified
“…Recientemente, Flores-Muñoz et al, mostró en su modelo experimental de ratas "strole-prone" espontáneamente hipertensas (SPSHR) que Ang-(1-9) administrada en dosis de 100 ng·Kg-1·min-1 no modificó la PAS 22 . Estos resultados difieren del efecto antihipertensivo observado para Ang-(1-9) probablemente, debido a la menor dosis de Ang-(1-9) usada en ratas SPSHR comparada con nuestros estudios de regresión de la HTA 23 . Por otra parte, los resultados del presente estudio muestran que la administración crónica de Ang-(1-9), en un modelo experimental de ratas previamente hipertensas, logró revertir la hipertrofia cardíaca, destacando que este efecto tampoco fue mediado por Ang-(1-7).…”
Section: Discussionunclassified
“…In turn, Ang 1-9 can be converted to Ang 1-7 by ACE [36]. Angiotensin 1-9 exerts beneficial effects on the heart, which consist in reduction of blood pressure, improvement of endothelial function and limitation of hypertrophy and fibrosis [38]. It has been suggested that these beneficial effects of Ang 1-9 can be achieved via angiotensin II type 2 receptor (AT2R), independently of its conversion to Ang 1-7 [38,39].…”
Section: Apelin/apj System Vs Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…Angiotensin 1-9 exerts beneficial effects on the heart, which consist in reduction of blood pressure, improvement of endothelial function and limitation of hypertrophy and fibrosis [38]. It has been suggested that these beneficial effects of Ang 1-9 can be achieved via angiotensin II type 2 receptor (AT2R), independently of its conversion to Ang 1-7 [38,39]. In addition to the favorable activity on cardiac dysfunction, ACE2 was reported to play a role in the hydrolysis of a large number of peptides, including apelin-13 and apelin-36, which are thus degraded to ineffective forms [40].…”
Section: Apelin/apj System Vs Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…5 Ang (1-9) also reduces cardiovascular damage induced both by hypertension 5 and myocardial infarction. 6 These beneficial effects of Ang (1-9) are mediated directly through binding to the AT2 receptor.…”
mentioning
confidence: 99%
“…In this issue of Hypertension, the role of dipeptidyl peptidase III (DPP III) as a new antihypertensive candidate has been characterized in the mice. 1 Similar to DPP III, the carboxy peptidase ACE2 mediates degradation from Ang II to Ang (1-7) and also from Ang I to Ang (1)(2)(3)(4)(5)(6)(7)(8)(9). Both peptides contribute to the antihypertensive/ vasoprotective effects of the counterregulatory RAAS pathway ( Figure).…”
mentioning
confidence: 99%